Precisely tailored shell thickness and Ln3+ content to produce multicolor emission from Nd3+-sensitized Gd3+-based core/shell/shell UCNPs through bi-directional energy transfer - Serge Correales, York E. [UNESP]; Hazra, Chanchal [UNESP]; Ullah, Sajjad; Lima, Laís R. [UNESP]; Ribeiro, Sidney J. L. [UNESP] (Royal Society of Chemistry (RSC), 2019)
Lanthanide (Ln3+)-doped upconversion nanoparticles (UCNPs) have been paid great attention as multiplexing agents due to their numerous uses in biological and clinical applications such as bioimaging and magnetic resonance imaging (MRI), to name a few. To achieve efficient multicolor emission from UCNPs under single 808 nm excitation and avoid detrimental cross-relaxations between the Ln3+ activator ions (positioned in either the core and/or shell in the core/shell), it is essential to design an adequate nanoparticle architecture. Herein, we demonstrate the tailoring of multicolor upconversion luminescence (UCL) from Nd3+-sensitized Gd3+-based core/shell/shell UCNPs with an architecture represented as NaGdF4:Tm3+(0.75)/Yb3+(40)/Ca2+(7)/Nd3+(1)@NaGdF4:Ca2+(7)/Nd3+(30)@NaGdF4:Yb3+(40)/Ca2+(7)/Nd3+(1)/Er3+(X = 1, 2, 3, 5, 7) [hereafter named CSS (Er3+ = 1, 2, 3, 5 and 7 mol%)]. Such UCNPs can be excited at a single wavelength (∼808 nm) without generation of any local heat. Incorporation of substantial Nd3+-sensitizers with an appropriate concentration in the middle layer allows efficient harvesting of excitation light which migrates bi-directionally across the core/shell interfaces in sync to produce blue emission from Tm3+ (activator) ions in the core as well as green and red emission from Er3+ (activator) ions in the outermost shell. Introduction of Ca2+ lowers the local crystal field symmetry around Ln3+ ions and subsequently affects their intra 4f-4f transition probability, thus enhancing the upconversion efficiency of the UCNPs. By simple and precise control of the shell thickness along with tuning the content of Ln3+ ions in each domain, multicolor UCL can be produced, ranging from blue to white. We envision that our sub-20 nm sized Nd3+-sensitized Gd3+-based UCNPs are not only potential candidates for a variety of multiplexed biological applications (without impediment of any heating effect), but also can act as MRI contrast agents in clinical diagnosis.